Negotiating the 'Impossible' Religion and Politics in the Tactical Works of Extramucadele - Gorgulu, Vehbi (Routledge Journals, Taylor & Francis Ltd, 2015)
This article evaluates how a tactical media practitioner challenges the status of iconised signs and symbols, by analysing works of Istanbul-based artist Extramucadele. The artist challenges the idolised and clashing national and religious symbols of Turkey's society and presents his works in forms of tactical media. By focusing on tactical media practices in the contemporary art scene of Turkey, this study aims to provide insights on how media activists point to the power of tactics as means of challenging established meanings associated with enduring signs and symbols.
Keywords: Vehbi Gorgulu; Extramucadele; Tactical Media; Media Activism; Jdp; Gezi Park; Memed Erdener; Michel De Certeau; Hasan Bulent Kahraman; Burak Delier